Participatory theatre and mental health recovery: a narrative inquiry - Torrissen, Wenche; Stickley, Theodore (SAGE, 2017)
Aims: To identify the potential relationship between participation in theatre and mental health recovery. To give voice to the stories told by participants of Teater Vildenvei, a theatre company that has been part of the rehabilitation programme for mental health service users in Oslo since 1995.